2013
DOI: 10.1080/15459624.2013.831986
|View full text |Cite
|
Sign up to set email alerts
|

Potential Exposures Associated with Indoor Marijuana Growing Operations

Abstract: We entered a total of 30 indoor marijuana grow operations (IMGO) with law enforcement investigators in order to determine potential exposures to first responders. Samples for airborne fungal spores, volatile organic compounds, carbon dioxide, carbon monoxide, and delta-9-tetrahydrocannabinol (THC) were obtained as well as the identification of chemicals utilized in the IMGO. The chemicals utilized within the IMGOs were primarily pesticides and fertilizers with none showing high toxicity. Although several of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 9 publications
(19 reference statements)
0
92
0
Order By: Relevance
“…The most frequently found mold species in our study, Penicillium sp. and Aspergillus sp., were also identified as the most frequent mold species in illicit indoor cannabis plantations in the USA (7,15) and Canada (5). In Canada, on cannabis flower buds, Aspergillus fumigatus was the most frequently found mold species (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently found mold species in our study, Penicillium sp. and Aspergillus sp., were also identified as the most frequent mold species in illicit indoor cannabis plantations in the USA (7,15) and Canada (5). In Canada, on cannabis flower buds, Aspergillus fumigatus was the most frequently found mold species (5).…”
Section: Discussionmentioning
confidence: 99%
“…They include the fungicides o‐phenylphenol, chlorothalonil, imazalil, propamocarb and tebuconazole; the pyrethroid insecticides bifenthrin, permethrin and cypermethrin; the neonicotinoid insecticide imidacloprid; and the acaricide bifenazate. Just as the latter authors, Cuypers et al , Martyny et al , and Van Dycke also found that most insecticides detected in cannabis plantations are pyrethroids, which have a low toxicity when inhaled or via dermal absorption.…”
Section: Hazards Of Indoor Cannabis Plantations As Reported In the LImentioning
confidence: 89%
See 1 more Smart Citation
“…Most critical, emerging adults with heavy use backgrounds show size effects in brain areas that are involved in cognition, such as the prefrontal cortex and parietal region [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Marijuana Use Modifies Brain Structure and Physiologymentioning
confidence: 99%
“…It is common to find much more THC and much less CBD per plant [6,7]. The problem of pesticide-contaminated marijuana also requires more research [8]. Pesticide has been detected on cannabis plants intended for commercial sale.…”
mentioning
confidence: 99%